Sistematic Literature Review : Dampak Stigma Masyarakat Terhadap Orang Dengan Gangguan Jiwa - Rinancy, Hariet (Sahabat Publikasi Kuu, 2024)
Community stigma towards people with mental disorders (ODGJ) is still widely found throughout the world, including Indonesia. Stigma can have a negative impact on the order of human life, including mental health services. This study aims to determine the impact of community stigma on ODGJ. The research method used was systematic literature review. The data base sources are google scholar, pubmed and science direct using the keywords impact, community stigma and people with mental disorders. 149 literature were obtained, then for the assessment of the quality of literature using the PRISMA method, and 6 literature were selected that met the inclusion criteria. The results of the study showed that all the literature stated that the impact of community stigma on ODGJ was not getting the right treatment and four literatures stated the disintegration of ODGJ with the community. Conclusion: The impact of community stigma towards ODGJ is that ODGJ do not get proper treatment, and it is even difficult to get proper treatment because ODGJ tend to be hidden, ostracized and even shackled. The next impact is that ODGJ experience disintegration with the community due to the labeling given by the community. Therefore, interventions are needed to increase community knowledge about the diagnosis of mental disorders, so that the community can accept ODGJ like other chronic disease sufferers and ODGJ can live more optimally like other members of the community.